2021
DOI: 10.1186/s13244-021-01134-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of computed tomography-based, artificial intelligence-driven waist skeletal muscle volume in uterine endometrial carcinoma

Abstract: Objectives To investigate the impact of computed tomography (CT)-based, artificial intelligence-driven waist skeletal muscle volume on survival outcomes in patients with endometrial cancer. Methods We retrospectively identified endometrial cancer patients who received primary surgical treatment between 2014 and 2018 and whose pre-treatment CT scans were available (n = 385). Using an artificial intelligence-based tool, the skeletal muscle area (cm2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Other studies on Asian patients reported that L3 sarcopenia, classified by the Q1 cutoff value, was an independent prognostic factor for worse DFS and OS in patients with colorectal cancer [ 22 24 ]. Only a few studies have reported that volumetric sarcopenia has a worse prognostic impact on gynecologic malignancies [ 8 9 29 ]. A single cross-sectional CT image at the L3 level, which reflects whole-body tissue quantities, is a well-established method for body composition analysis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies on Asian patients reported that L3 sarcopenia, classified by the Q1 cutoff value, was an independent prognostic factor for worse DFS and OS in patients with colorectal cancer [ 22 24 ]. Only a few studies have reported that volumetric sarcopenia has a worse prognostic impact on gynecologic malignancies [ 8 9 29 ]. A single cross-sectional CT image at the L3 level, which reflects whole-body tissue quantities, is a well-established method for body composition analysis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…MD decreases with the worsening of myosteatosis [ 21 ]. The volumetric skeletal muscle index (SMI) was calculated as the waist muscle volume (cm 3 ) divided by height (m 3 ) [ 8 9 ]. Few studies have been conducted on volumetric parameters; therefore, the optimal cut-off values of SMI and MD for sarcopenia and myosteatosis were set as the Q1 values by referring to another study [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding reviews and opinion letters, 33 original articles were identified. This list was further filtered and narrowed down to 10 relevant original articles dealing with AI and medical images developments [14][15][16][17][18][19][20][21][22][23]. The selected papers were critically assessed for compliance with each item included in the MAIC-10 checklist.…”
Section: Methodsmentioning
confidence: 99%